Assessment of Funding Approach to Adult Learning and Education in Rural Communities - Ojobanikan, Emmanuel Idowu; Mandah, Njitum C. A.; Foyewa, Abosede Olubukola (MO.RI Publishing, 2024)
The challenges of Nigeria as a nation require holistic approach and appropriate education to tackle for socio-economic development and peaceful co-existence of Nigerians. Adult learning and education (ALE) being a discipline with huge potentials for adults, is capable of tackling the problems. However, it needed to be scaled up through new initiatives and approaches. This study therefore, assessed the funding approach to ALE programmes in Ekiti State, Nigeria; with a view to understand how ALE programmes have been funded and implemented in Nigeria in recent times. Review of concepts and terms were carried out. Qualitative research method was used to obtain data. It was discovered that Ekiti state Government adopted specific need and service-oriented approach to funding and implementation of adult learning and education programmes in the State. The approach yielded positive results with 67 adult literacy centres established and 5,029 adult learners enrolled between 2019 and 2022. A total of 45 individuals and 12 faith based organisations sponsored ALE programmes. It is therefore recommended that government at all levels should adopt need and service-oriented approach to funding and implementation of ALE programmes with a view to make ALE relevant in providing solution to the Nigeria’s socio-economic, political, environmental and security challenges.